An Inductive Approach to Examining the Morphophonology of Polymorphemic Words in Indonesian - Yusuf, Cahyo; Irawan, Yusup; Lubna, Syarifah; Sariasih, Yanti; Mazid, Sukron; Wulansari, Atsani (International Journal of Language Education, 2025)
This study investigates the morphophonological process in Indonesian, with particular focus on the polymorphemic construction {kә-base morpheme-an}. The research adopts an inductive approach, supported by acoustic data analysis, to identify shifts and sound changes during word decomposition. The findings reveal the vowel alternations, in which [i] and [u] in the penultimate syllable nucleus are realized allophonically as [I] and [U] in the final syllable nucleus of the stem. Consonant changes are also observed, such as the phoneme /k/ in the coda of a final syllable shifting to /ʔ/ in the coda of the base morpheme, as well as the change from /x/ to /h/. These shifts and alternations can be categorized as substantial substitutions, motivated by morphological factors. The study demonstrates that an inductive approach to morphophonological processes enriches linguistic inquiry and offers pedagogical implications, offering new perspectives on the interaction between phonology and morphology.